Elements for a history of sources and stemmas in the work of José Maurício Nunes Garcia (Per Musi, 2019)
tarting from a rereading of the thematic Catalog produced by Cleofe Person de Mattos (1970), this work reflects on informational elements extracted from other catalogs and also from handwritten musical sources that transmit the work of José Maurício Nunes Garcia, existing in collections such as the Dom Oscar Collection (Mariana’s Museum of Music) and the Francisco Curt Lange Collection (Inconfidência’s Museum of Ouro Preto). Based on these reflections, the author discusses the relationships among such sources, their scribes, their circulation among the institutions, in order to contribute to the elaboration of consistent descriptions for the search instruments (inventories, catalogs, databases, etc.) that allow both an exhaustive census of the sources for the elaboration of stemmas oriented to the work of critical editions, as well as a history of the Mauritian sources.